Analysis Connection between Liquidity and Activities to Profitability at PT. FKS Multi Agro Tbk - Pasomba', Jelnia Nu'tu; Paridi, Andryanus; Todingbua, Manuel A. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Study This analyze connection between liquidity and activity to profitability at PT FKS Multi Agro Tbk during 2019–2023 period . The data used is secondary data in the form of report finance quarterly earnings​ from the Indonesia Stock Exchange . Variables liquidity measured through the current ratio, quick ratio, and cash ratio, while activity measured use ratio rotation assets , inventory , receivables , and assets fixed . Profitability analyzed through ROA, ROE, and NPM ratios . The approach used is analysis ratio financial analysis and Partial Least Square (PLS) test. Research results show that Good liquidity and activity own influence positive significant to profitability . In 2022, it was recorded as period with efficiency assets and profitability highest , while in 2023 it will occur decline in some indicator , shows the need optimization management assets and cash. Findings This give implications important for management company agribusiness For guard balance between liquidity and efficiency operations to improve performance finance in a way sustainable .